Metal‐Centered Zintl Ions Isolated by Direct Extraction from Endohedral Intermetallic Precursor: [Co1–x@Sn9]4– (x ≈ 0.32) and [Co2@Sn17]5–12. Issue 14 (6th October 2014) - He, Haiyan; Klein, Wilhelm; Jantke, Laura‐Alice; Fässler, Thomas F.
Abstract Two new compounds with Co‐centered Sn9 clusters were obtained by the extraction directly from the intermetallic precursor K4.79Co0.79Sn9 in ethylenediamine with addition of cryptand [2.2.2]. The anions [Co0.68@Sn9]4– in K[K([2.2.2]crypt)]3[Co0.68@Sn9] (1) consisting of overlaying [Co@Sn9]4– and [Sn9]4– cluster anions are connected by K atoms to form infinite <alternatives> <![CDATA[$\rm^{1}_{\infty}$]]> <inline-graphic xlink:href="ark:/27927/pgh2cqw68s7" mimetype="image" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" /></alternatives>K[Co0.68@Sn9] chains. The anions [Co2@Sn17]5– in [K([2.2.2]crypt)]5[Co2@Sn17]·en·tol (2) are built from two [Co@Sn9] sharing one common Sn atom, with the same composition but a different conformation as in the previously reported [K([2.2.2]crypt)]5[Co2@Sn17]. Quantum chemical calculations for the different conformers of [Co2@Sn17]5– reveal that both conformers are rather close in energy and that the short intercluster Sn–Sn distance in 2 does not originate from attractive interactions.